Pengaruh Kompensasi Eksekutif, Koneksi Politik, dan Capital Intensity pada Tax Avoidance - Apsari, A. A. Ayu Nur Cintya; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2018)
This study aims to determine the effect of executive compensation, political connections, and capital intensity on tax avoidance. This research was carried out on property, real estate, and building construction companies listed on the Indonesia Stock Exchange in 2014-2016. The number of samples used in this study were 12 companies with the number of observations 36. The method of determining the sample of this study was non-probability sampling with purposive sampling technique. Data analysis techniques were carried out using multiple linear regression analysis techniques. The results showed that executive compensation had a negative and significant effect on tax avoidance. This study also found that political connections and capital intensity have a negative and not significant effect on tax avoidance. Keyword: Executive Compensation, Political Connections, Capital Intensity, Tax Avoidance